DISCRETE RESONANT ABSORPTION IN MOLECULAR NANOFILMS - Vucenovic, Sinisa M; Vojnović, Matilda (NBP. Nauka, bezbednost, policija, 2019)
We have analyzed the significant different optical absorption of molecular nano film crystalline formations. The main reason for this behavior is in existence of boundaries on the film structures and we needed to investigate these properties theoretically. In this process, we have done some combination of (where possible) analytical calculations and (in other cases) numerical calculations. We have calculated allowed energies of exciton (quasi)particles, and their appearance in nano films but in particular direction - perpendicular to the surface of the film. We have analyzed why in film appear surface exciton localization, and after that calculated dielectric permittivity and optical indices (absorption and refraction). We have established that boundary parameters greatly influence onto optical phenomena. This influence is resonant, i.e. frequency related and selectable (depend on what layer is calculated). We even found the some particular conditions for the appearance of one (single) absorption line.